Postoperative Symptom Cluster in NSCLC Patients and Its Relationship with Social Support and Self-Efficacy: A Cross-Sectional Study - Cao J; Chen K; Gao L; Yang D; Zhang W; Deng X; Liu C; Dai Q; Xu X; Li F (Risk Management and Healthcare Policy)
Juan Cao,1,* Keyu Chen,1,* Lihong Gao,1 Dandan Yang,1 Wenjuan Zhang,1 Xiaheng Deng,1 Changpeng Liu,2 Qi Dai,1 Xinyi Xu,3 Fang Li4 1Jiangsu Province Hospital and the First Affiliated Hospital with Nanjing Medical University, Thoracic Surgery, Nangjing, People’s Republic of China; 2The Affiliated Cancer Hospital of Zhengzhou University, Zhengzhou, People’s Republic of China; 3Nanjing Medical University, School of Nursing, Nanjing, People’s Republic of China; 4Jiangsu Province Hospital and the First Affiliated Hospital with Nanjing Medical University, Nursing Department, Nangjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinyi Xu, Email 912446750@qq.com Fang Li, Email srylifang@163.comPurpose: The study aimed to identify symptom clusters among NSCLC patients within 3 months postoperatively and analyze the relationships between symptom clusters and social support and self-efficacy.Methods: We conducted a cross-sectional study from January 1 to May 31, 2024, involving NSCLC patients undergoing surgery at hospitals in Jiangsu Province. Data were collected using the MD Anderson Symptom Inventory, the Perceived Social Support Scale (PSSS), and the Strategies Used by People to Promote Health (SUPPH).Results: Exploratory factor analysis revealed five distinct symptom clusters: respiratory distress, respiratory tract discomfort, physical exhaustion, digestive dysfunction, and nighttime disturbances. The severity of physical exhaustion and nighttime disturbances was negatively correlated with PSSS scores. Conversely, the severity of respiratory distress, respiratory tract discomfort, and digestive dysfunction symptoms was negatively correlated with SUPPH scores.Conclusion: Our findings may guide medical professionals in managing postoperative symptoms in NSCLC patients. Social support and self-efficacy appear to be significant factors influencing the severity of symptom clusters.Keywords: NSCLC, symptom clusters, social support, self-efficacy, cross-sectional survey